HPTLC Method for the Analysis of Melatonin in Bulk and Pharmaceutical Formulations - P. Agarwal, Suraj; J. Gonsalves, Harrina; K. Khar, Roop (Asian Journal of Chemistry, 2010)
A simple, precise and stability-indicating high performance thin-layer chromatographic method of analysis of melatonin both as bulk drug and in pharmaceutical formulation was developed and validated. The method employed TLC aluminium plates precoated with silica gel 60F-254 as the stationary phase and mobile phase comprising toluene:ethyl acetate:formic acid (5:4.5:0.5 v/v). Densitometric analysis of melatonin was carried out in the absorbance mode at 290 nm. The linear regression analysis data for the calibration plots showed good linear relationship with r = 0.9989, with respect to peak area, in the concentration range 100-600 ng/ spot. The method was validated for precision, specificity, recovery and robustness. The recovery of the drug from tablets carried out by standard addition method was found to be 99.72 ± 0.682. Statistical analysis proves that the method is repeatable, selective and accurate for the estimation of the drug. Forced degradation studies showed the effect of variations in pH, UV light and high temperature on the stability of melatonin. As the proposed method could effectively separate the drug from its degradation products, it can be employed as a stabilityindicating method.